The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/jsss-4-263-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia storage studies on H-ZSM-5 zeolites by microwave cavity perturbation: correlation of dielectric properties with ammonia storage

Abstract: Abstract.To meet today's emission standards, the ammonia-based selective catalytic reduction (SCR) has become the major NO x control strategy for light and heavy diesel engines. Before NO x reduction can proceed, adsorption of ammonia on the acidic sites of the catalyst is necessary. For improvements in efficiency and control of the exhaust gas aftertreatment, a better understanding of the ammonia storage on the acidic sites of zeolite-based SCR catalysts is needed. Thereby, the correlation of dielectric prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…(1), this is caused by an increase in the permittivity of the sensitive layer. Thus, these measurements are consistent with the results of previous research (Dietrich et al, 2017;Rauch et al, 2017). The increase in sensor temperature results in a significantly lower resonant frequency shift.…”
Section: Temperature Dependence Of the Ratio Between Strongly And Weasupporting
confidence: 92%
See 2 more Smart Citations
“…(1), this is caused by an increase in the permittivity of the sensitive layer. Thus, these measurements are consistent with the results of previous research (Dietrich et al, 2017;Rauch et al, 2017). The increase in sensor temperature results in a significantly lower resonant frequency shift.…”
Section: Temperature Dependence Of the Ratio Between Strongly And Weasupporting
confidence: 92%
“…It has already been successfully demonstrated that the stored ammonia in zeolite-based selective catalytic reduction (SCR) catalysts can be determined using a radio-frequency-based technology. The excitation and measurement of the resonances was carried out in a contactless way by coaxial probe antennas in a cavity resonator, which is formed by the metallic catalyst canning (Dietrich et al, 2017). This was possible since the ammonia storage in the zeolite structure causes a change in the complex permittivity ε = ε −j ε (Rauch et al, 2017).…”
Section: Sensing Principlementioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the microwave cavity perturbation technique can be used to effectively characterise solid-state ammine materials, including the determination of ammonia stoichiometry when appropriately calibrated. 9,[41][42][43] This technique provides a non-invasive, nondestructive method of measuring the intrinsic dielectric properties of solid-state materials as they absorb ammonia gas, and is effective as ammonia is a highly polar molecule with an electric dipole moment of 1.47 D. 44 The absorption of ammonia within the solid matrix causes a change in the polarisation (quantified by e 1 ) of the sample, which can be seen as a shift in the resonant frequency (Df 0 ) of the microwave cavity resonator (MCR) from when it is empty ( f 0 ), with chemisorbed (strongly bound to metal centres) ammonia causing the greatest perturbation in polarisation. 9 Changes in dielectric loss (quantified by e 2 ), are most closely associated with physisorbed (weakly bound to surfaces) ammonia 9 and cause a change in the resonant bandwidth of the system (Df B ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great academic and technological interest to gain in depth information on the proton transport properties of these Cu-promoted zeolites, as well as on the impact of proton transport in the direct electrical determination of stored NH3 and in the electrical in operando monitoring of NH3-SCR catalysis [28,29].…”
Section: Introductionmentioning
confidence: 99%